Activities of daily living at hospital admission and estimated survival time of older patients. (28th November 2020) - Ryg, Jesper; Engberg, Henriette; Anru, Pavithra Laxsen; Pedersen, Solvejg Gram Henneberg; Jorgensen, Martin Gronbech; Vinding, Kirsten Laila; Masud, Tahir; Andersen-Ranberg, Karen
Abstract: Background: Predicting expected survival time in acutely hospitalised older patients is a clinical challenge. Objective: To examine if activities of daily living (ADL) assessed by Barthel-Index-100 (Barthel-Index) at hospital admission adds useful information to clinicians on expected survival time in older patients. Methods: A nationwide population-based cohort study was used. All patients aged ≥65 years in the National Danish Geriatric Database from 2005 to 2014 were followed up until death, emigration or study termination (31 December 2015). Individual data were linked to national health registers. Barthel-Index was categorised into five-point subcategories with a separate category of Barthel-Index = 0. Kaplan–Meier analysis was used to assess crude survival proportions (95% CI) and Cox regression to examine association of Barthel-Index and mortality adjusting for age, Charlson comorbidity index, medication use, BMI, marital status, prior hospitalisations and admission year. Results: In total, 74, 589 patients (63% women) aged (mean (SD)) 82.5(7.5) years with Barthel-Index (median (IQR)) 54(29-77) were included. In patients with Barthel-Index = 100-96 crude survival was 0.96(0.95-0.97) after 90-days, 0.88(0.87-0.89) after 1-year, and 0.79(0.78-0.80) after 2-years. Corresponding survival in patients with Barthel-Index = 0 was 0.49(0.47-0.51), 0.35(0.34-0.37) and 0.26(0.24-0.27). Decreasing Barthel-Index was associated with increasing mortality in the multivariable analysis. In women with Barthel-Index = 0, the mortality risk (HR (95% CI)) was 14.74(11.33-19.18) after 90-days, 8.40(7.13-9.90) after 1-year and 6.22(5.47-7.07) after 2-years using Barthel-Index = 100-96 as reference. In men, the corresponding risks were 11.36(8.81-14.66), 6.22(5.29-7.31) and 5.22(4.56-5.98). Conclusions: ADL measured by Barthel-Index provides useful, easily accessible and independent information to clinicians on expected survival time in patients admitted to a geriatric department.